Use of and Preference for Traditional Foods among the Belcher Island Inuit - Wein, Eleanor E.; Freeman, Milton M.R.; Makus, Jeanette C. (ARCTIC, 1996)
To document the extent of use of traditional foods (marine and land mammals, birds, fish, and plants) and degree of preference for these foods in contemporary diets and culture, 102 households (98% of Inuit households) in the community of Sanikiluaq, Northwest Territories, Canada, were studied. During personal interviews, individuals estimated their frequency of use of traditional foods, systematically by season. In addition, 100 adults (from 96% of households) and 64 young people (84% of those in Grades 6-11) rated 41 foods (32 traditional and 9 market foods) for preference on a 5-point hedonic scale. According to respondents' estimates, traditional foods were used by all households, on average 1171±852 times annually. Fish and shellfish were most frequently consumed (523±490 times annually), followed by birds (254±204), sea mammals (184±161), berries (166±115), and land mammals (45±70). Preference ratings showed that most traditional foods were well-liked by both adults and young people, although adults rated 25 traditional foods higher (p<0.01) and 2 market foods lower (p<0.01) than young people did. Traditional foods remain an important part of contemporary Sanikiluaq lifestyle. Afin de documenter l'importance de l'utilisation des aliments traditionnels (mammifères marins et terrestres, oiseaux, poissons et plantes) et le degré de préférence pour ces aliments dans les régimes alimentaires et la culture actuels, on a fait une étude auprès de 102 foyers (98 p. cent de foyers inuit) dans la collectivité de Sanikiluaq (Territoires du Nord-Ouest [Canada]). Au cours d'interviews individuelles, les personnes estimaient la fréquence de leur utilisation des aliments traditionnels, de façon systématique, sur une base saisonnière. En outre, 100 adultes (provenant de 96 p. cent des foyers) et 64 jeunes (dont 84 p. cent scolarisés de la 6e à la 11e année) ont classé 41 aliments (32 traditionnels et 9 commerciaux) selon leur préférence sur une échelle hédonique de 5 points. Selon l'évaluation des répondants, les ...